Emotional Competencies of Higher Education Students in Virtual Modalities in the Post-Pandemic Period: A Systematic Review - López-Bustamante, Gisela Elízabeth (2025)
Introduction. The development of emotional competencies (EC) in education is essential in the teaching-learning processes, and with greater emphasis in virtual environments, which gained greater prominence during the COVID-19 pandemic and have become permanently integrated into the current educational landscape. Academic publications examine this competence from multiple approaches, highlighting its relevance; however, the available studies remain insufficient, especially those focused on higher education. Objective. This systematic literature review seeks to analyze the scientific production on the EC of higher education students in virtual modalities in the post pandemic period. Methodology. A systematic review of studies published in 2022 and 2023 was conducted following the PRISMA protocol; twenty articles were selected from the Taylor & Francis Online database. Results. Asia accounts for 45% of the studies, representing the highest number of publications, whereas the absence of Latin American countries is notable. Ambiguity is evidenced in the theoretical positioning used to define the concepts, and a gap is observed in the theoretical-scientific foundation that allows for the differentiation between emotional intelligence and EC. Conclusions. Three categories associated with virtual education and EC were identified: (1) the relationship between academic engagement and emotional intelligence, (2) the importance of academic engagement linked to EC, and (3) the relevance of technological competencies and their relationship with EC. Recommendations. The study recommends increasing theoretical-conceptual and systematic review research focused on the development of EC within virtual education.